Charles J. Adam's Framework for the Study of Religion - Shobirin, Abdurrahman; Aziz, Ahmad Fakhril; Abdurochman, Hikmat; Fadhlan, Muhammad (Indonesian Journal of Islamic Education and Local Culture, 2023)
Charles J. Adams' concern about methods and approaches to the study of Islam is an academic concern about the failure of historians of religion to expand our knowledge and understanding of Islam as a religion, and experts on Islam (Islamists) to explain precisely the phenomenon of Islamic religiosity. To answer this academic anxiety, Charles J. Adam uses two disciplines, namely the history of religion and Islamic studies as a theoretical framework or framework (conceptual tool). To analyze the two disciplines, he uses two approaches, namely a normative or religious approach and a descriptive approach. The scope of his study consists of the study of Pre-Islamic Arabia, the Study of the Life of the Prophet Muhammad, the Study of the Qur'an, the Study of Hadith, the Study of Kalam Science, the Study of Sufism, the Study of the Shi'a School, Popular Religion, the Study of Worship, the Study of Philosophy, and the Study of Islamic Law. The major contribution of Adams' thought is to provide a distance between the normative approach that has a religious commitment in conducting research and the descriptive approach that has no religious commitment. The study of his thoughts on Islam has received some criticism and support. Among them is M. Amin Abdullah, who thinks that Charles J. Adams' thinking produces an understanding of Historicity-Profanity and Interconnectedness.